Mechanical factors associated with the development of training volleyballs - Ho, C.-S.; Lin, K.-C.; Chen, K.-C.; Yan, Z.-T.; Chang, C.-H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
The objectives of this study were to assess volleyball speed and impact force and to analyse the differences between these properties. Three types of volleyballs were used in this study: MVA200, weighing 270 ± 10 g; Prototype Ball A (Type A), weighing 270 ± 10 g; and Prototype Ball B (Type B), weighing 340 ± 10 g. Vertically downward 3-m impact tests were conducted using a serving machine, force plate, and radar speed gun. Contact time, ball speed, mean force, peak force, total impulse, initial momentum, incident impulse, and lost momentum were calculated. Intraclass correlation coefficients were calculated to evaluate the reliability of the data, and one-way analysis of covariance and Scheffe`s post hoc analysis were used to analyse the variables of the three ball types. The paired samples t-test was used to compare the difference between initial momentum and incident impulse. The results indicated that the intraclass correlation coefficients of the three ball types were 0.998 (MVA200), 0.997 (Type A), and 0.999 (Type B). Type B considerably surpassed Type A and MVA200 in mechanical factors, and Type A was significantly superior to MVA200 in incident impulse and lost momentum. The results indicated that different volleyballs of the same size, weight, and internal air pressure have dissimilar mechanical features and implied that slight adjustment to ball structure can cause substantial changes in the specific characteristics. In addition, the mass increased the lost momentum, which might cause the ball to bounce unpredictably.